Regression analysis of the relationship between economic growth and foreign aid in Africa - Ngango, Jean Gabin; Bašta, Milan; Helman, Karel; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2021)
This thesis explores the impact of foreign aid on growth in Africa. It focuses on whether foreign aid has an effect on capital accumulation and GDP growth. The dataset spans five years, from 2014 to 2018 for 44 countries. According to the regression results, foreign aid has non-linear relationship with economic growth. Foreign aid has a significant impact on investment and economic growth with diminishing returns. Foreign aid has no significance impact on saving as it fails to impact incentives to when choosing between present and future consumption.
Vedoucí práce: Milan Bašta
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: quantitative economic analysis [obor dipl. práce]; diplomové práce; master's theses